On the Relationship between Forward and Backward Gapping. (16th January 2018) - Citko, Barbara
Abstract: This article examines the relationship between forward and backward gapping, based on the evidence from Polish, a language that allows both types. The two types of gapping differ with respect to polarity mismatches, word order, compatibility with relational modifiers, cumulative agreement, and the ability to gap subconstituents. However, they pattern together with respect to inflectional mismatches, preposition stranding, and the behavior of the remnants with respect to movement constraints. Both the differences and the similarities are argued to follow from two distinct derivations, in which forward gapping involves ellipsis (resulting in two copies of the gapped string), whereas backward gapping involves a multidominant structure with the gapped string being literally shared between the two conjuncts (resulting in a single copy).